Enhanced photovoltaic performance of dye sensitized solar cell using TiO2 and ZnO nanoparticles on top of free standing TiO2 nanotube arrays. (April 2017) - Chamanzadeh, Z.; Noormohammadi, M.; Zahedifar, M.
Abstract: Photovoltaic performance of dye sensitized solar cell (DSSC) with absorber layer of TiO2 nanotube (NT)/TiO2 nanoparticles (NPs)/ZnO NPs was investigated. Fabricated DSSC exhibits enhanced open circuit voltage, current density and power conversion efficiency compared with DSSC having absorber layer of TiO2 NT/ TiO2 NPs and TiO2 NT/ZnO NPs. To further explore the dynamics of charge transport and recombination processes, electrochemical impedance analysis, intensity modulated photovoltage spectroscopy and photocurrent spectroscopy were carried out on the fabricated DSSCs. It was found that an optimal combination of TiO2 /ZnO NPs on top of TiO2 NTs reduces the electron recombination and improves transport pathways, resulting in an efficient charge collection of 99%.